2012
DOI: 10.1016/j.joms.2012.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Does Swallowing Function Recover in the Long Term in Patients With Surgically Treated Tongue Carcinomas?

Abstract: 1Abstract Purpose: The present study aims to measure the post-surgical swallowing function in patients five years after operative treatment of tongue carcinoma.Patients and Methods: Using a retrospective cohort study design, the investigators enrolled post-surgical patients treated for tongue carcinomas in Hokkaido University Hospital. The primary outcome variable was the Oropharyngeal Swallow Efficiency (OPSE) determined by videoflluoroscopic evaluation and the OPSE at present was compared with that at discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Devine et al reported that the MLR approach is associated with slightly worse oral motoresensory functions, such as mastication, swallowing, and speech, compared to the MS approach, probably due to the fact that the mylohyoid and digastric muscles attached to the mandible are transected in the MLR approach (Devine et al, 2001). Another fact disfavoring the MLR approach is that simultaneous reconstruction of a tongue defect, especially flap transfer, is technically difficult in this approach because of the presence of an intact mandible (Kruse et al, 2011;Cantù et al, 2006;Dziegielewski et al, 2010;Tei et al, 2012). However, our results show that in the scenario of compartmental tongue surgery, the MLR approach resulted in oral motoresensory restoration similar to that with the MS approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devine et al reported that the MLR approach is associated with slightly worse oral motoresensory functions, such as mastication, swallowing, and speech, compared to the MS approach, probably due to the fact that the mylohyoid and digastric muscles attached to the mandible are transected in the MLR approach (Devine et al, 2001). Another fact disfavoring the MLR approach is that simultaneous reconstruction of a tongue defect, especially flap transfer, is technically difficult in this approach because of the presence of an intact mandible (Kruse et al, 2011;Cantù et al, 2006;Dziegielewski et al, 2010;Tei et al, 2012). However, our results show that in the scenario of compartmental tongue surgery, the MLR approach resulted in oral motoresensory restoration similar to that with the MS approach.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the MLR approach, the lower lip and the mandible remain intact, and the mylohyoid muscles and hyomandibular furrow are incised to retract the tongue from the submandibular triangle for resection. Findings in the current literature are contradictory with regard to whether the MLR approach is superior to the MS approach in terms of surgical effectiveness, morbidity, functional recovery, esthetic appearance, survival, and QoL, or vice versa (Devine et al, 2001;Cantu et al, 2006;Dziegielewski et al, 2010;Karatzanis et al, 2012;Tei et al, 2012).…”
Section: Introductionmentioning
confidence: 97%